(untitled) (Research, Society and Development, 2021)
The objective of this work was to collect and identify native species of the florist composition in two different areas in the city of Salgueiro-PE. The collection was carried out in the municipality of Formiga, in an area of ​​preserved native forest and in the Uri site, where the degraded area was seen. In all areas, 2 rectangular transects (10x30m) were demarcated and distributed around each area, each transect was composed of three quadrangular plots (10x20m) separated by an interval of 10m. 102 species were collected in the degraded area and distributed in botanical families. In the preserved area, 375 individuals belonging to different families and species were found, having a greater number of species, that is, greater biodiversity and a rich variety of trees and shrubs in relation to the degraded area. The Shannon-Weaver (H’) value found in the degraded area (A) 1.75 and in the preserved area (B) 2.51, indicating that area B is more diverse and that A. What about Simpson’s dominance index (C) the observed value was 0.90 in area (A) and 0.76 in area (B). The observed values ​​of evenness were 0.90 for the preserved area and 0.84 for the degraded area, that is, the low value reflects that there is less uniformity regarding the plant distribution in the degraded area. According to the diversity indices, we can see that the degraded area loses its diversity in species, that is, it loses its richness that can influence the characteristics of the soil, fauna and biotic and abiotic interactions.